The twin risks in the dollarization debate: country and devaluation risks - Druck, Pablo (2001)
This paper discusses dollarization from the perspective of the relation between country and devaluation risk. In the absence of balance sheet effects, we find that a full dollarization of an economy increases its country risk. On the other hand, when balance sheet effects are present, the full dollarization could reduce country risk. The link between these two risks is based on the government's financial needs. In this paper government devalue the currency for fiscal purposes. Consequently, a full dollarization closes this avenue transferring the whole cost to bond holders. This paper stresses the idea that dollarization is at the very end a fiscal issue. Empirically, using the ratio of foreign currency deposit on total deposits as a proxy to the balance sheet effect, the paper tests the importance of this variable on country risk. We find that the balance sheet has a positive effect on country risk, in other words, country with higher balance sheet effect should have higher country risk.